Activation and Deactivation of Phillips Catalyst for Ethylene Polymerization Using Various Activators. Issue 3 (10th October 2016) - Zeng, Yanning; Chammingkwan, Patchanee; Baba, Ryuki; Taniike, Toshiaki; Terano, Minoru
Abstract : Though not necessarily required, metal alkyl activators can modulate the performance of a Phillips catalyst in ethylene polymerization. The type of aluminum alkyl greatly affects a tradeoff between the catalyst activation and deactivation, where bulky alkyl groups exhibit preferential suppression of the deactivation to give the highest activity and the widest operation window. Abstract : The present article reveals important roles of metal alkyl activators in tuning the performance of the Phillips catalyst in ethylene polymerization. The addition of aluminum alkyl aids the activation of the catalyst, while excess addition leads to the loss of the activity. The balance between the activation and deactivation depends on the type of employed aluminum alkyl, and tri‐ n ‐octylaluminum offers the most efficient catalyst usage by preferentially suppressing the deactivation. The passivation of aluminum trialkyl with a hindered phenol mildens not only the deactivation but also chain transfer reactions, leading to an increment of high molecular weight fractions.